Relating spatial perspective taking to the perception of other's affordances: providing a foundation for predicting the future behavior of others - Creem-Regehr, Sarah H.; Gagnon, Kyle T.; Geuss, Michael N.; Stefanucci, Jeanine K. (Frontiers in Human Neuroscience, 2013)
Understanding what another agent can see relates functionally to the understanding of what they can do. We propose that spatial perspective taking and perceiving other’s affordances, while two separate spatial processes, together share the common social function of predicting the behavior of others. Perceiving the action capabilities of others allows for a common understanding of how agents may act together. The ability to take another’s perspective focuses an understanding of action goals so that more precise understanding of intentions may result. This review presents an analysis of these complementary abilities, both in terms of the frames of reference and the proposed sensorimotor mechanisms involved. Together, we argue for the importance of reconsidering the role of basic spatial processes to explain more complex behaviors.